Epidemiological and microbiological characteristics of S. aureus pediatric infections in Colombia 2018–2021, a national multicenter study (Staphylored Colombia) - Gutierrez-Tobar, Ivan; Carvajal, Cristobal; Vasquez-Hoyos, Pablo; Díaz-Díaz, Alejandro; Londono Ruiz, Juan Pablo; Andrade, Joam; Camacho-Cruz, Jhon; Restrepo-Gouzy, Andrea; Trujillo-Honeysberg, Monica; Mesa-Monsalve, Juan Gonzalo; Perez, Ignacio; Von Moltke, Richard; et al. (Frontiers in Pediatrics, 2024)
BBACKGROUND: Staphylococcus aureus infections are a significant cause of morbidity and mortality in pediatric populations worldwide. The Staphylo Research Network conducted an extensive study on pediatric patients across Colombia from 2018 to 2021. The aim of this study was to describe the epidemiological and microbiological characteristics of S. aureus in this patient group. METHODS: We analyzed S. aureus isolates from WHONET-reporting centers. An "event" was a positive culture isolation in a previously negative individual after 2 weeks. We studied center characteristics, age distribution, infection type, and antibiotic susceptibilities, comparing methicillin sensitive (MSSA) and resistant S. aureus (MRSA) isolates. RESULTS: Isolates from 20 centers across 7 Colombian cities were included. Most centers (80%) served both adults and children, with 55% offering oncology services and 85% having a PICU. We registered 8,157 S. aureus culture isolations from 5384 events (3345 MSSA and 1961 MRSA) in 4,821 patients, with a median age of 5 years. Blood (26.2%) and skin/soft tissue (18.6%) were the most common infection sources. Most isolates per event remained susceptible to oxacillin (63.2%), clindamycin (94.3%), and TMP-SMX (98.3%). MRSA prevalence varied by city (<0.001), with slightly higher rates observed in exclusively pediatric hospitals. In contrast, the MRSA rate was somewhat lower in centers with Antimicrobial Stewardship Program (ASP). MRSA was predominantly isolated from osteoarticular infections and multiple foci, while MSSA was more frequently associated with recurrent infections compared to MRSA. CONCLUSIONS: This is the largest study of pediatric S. aureus infections in Colombia. We found MSSA predominance, but resistance have important regional variations. S. aureus remains susceptible to other commonly used antibiotics such as TMP-SMX and clindamycin. Ongoing monitoring of S. aureus infections is vital for understanding their behavior in children. Prospective studies within the Staphylored LATAM are underway for a more comprehensive clinical and genetic characterization.